Pyruvate kinase deficiency in children. Issue 9 (14th June 2021) - Chonat, Satheesh; Eber, Stefan W.; Holzhauer, Susanne; Kollmar, Nina; Morton, D. Holmes; Glader, Bertil; Neufeld, Ellis J.; Yaish, Hassan M.; Rothman, Jennifer A.; Sharma, Mukta; Ravindranath, Yaddanapudi; Wang, Heng; et al.
Abstract: Background: Pyruvate kinase deficiency (PKD) is a rare, autosomal recessive red blood cell enzyme disorder, which leads to lifelong hemolytic anemia and associated complications from the disease and its management. Methods: An international, multicenter registry enrolled 124 individuals younger than 18 years old with molecularly confirmed PKD from 29 centers. Retrospective and prospective clinical data were collected. Results: There was a wide range in the age at diagnosis from 0 to 16 years. Presentation in the newborn period ranged from asymptomatic to neonatal jaundice to fulminant presentations of fetal distress, myocardial depression, and/or liver failure. Children <5 years old were significantly more likely to be transfused than children >12 to <18 years (53% vs. 14%, p  = .0006), which correlated with the timing of splenectomy. Regular transfusions were most common in children with two severe PKLR variants. In regularly transfused children, the nadir hemoglobin goal varied considerably. Impact on quality of life was a common reason for treatment with regular blood transfusions and splenectomy. Splenectomy increased the hemoglobin and decreased transfusion burden in most children but was associated with infection or sepsis (12%) and thrombosis (1.3%) even during childhood. Complication rates were high, including iron overload (48%), perinatal complications (31%), and gallstones (20%). Conclusions: There is a high burden of disease in children with PKD, with wide practice variation in monitoring and treatment. Clinicians must recognize the spectrum of the manifestations of PKD for early diagnostic testing, close monitoring, and management to avoid serious complications in childhood.